Wilm’s tumor 1 promotes memory flexibility - Chiara Mariottini (Nature Portfolio, 2019)
Impairments in memory flexibility are associated with neuropsychiatric disorders such as PTSD and autism. Here, the authors report that the transcriptional repressor Wilm's Tumor 1 regulates synaptic plasticity leading to weakening of memory strength and enabling memory flexibility.